Infected dendritic cells facilitate systemic dissemination and transplacental passage of the obligate intracellular parasite Neospora caninum in mice. - Esther Collantes-Fernandez (Public Library of Science (PLoS), 2012)
The obligate intracellular parasite Neospora caninum disseminates across the placenta and the blood-brain barrier, to reach sites where it causes severe pathology or establishes chronic persistent infections. The mechanisms used by N. caninum to breach restrictive biological barriers remain elusive. To examine the cellular basis of these processes, migration of different N. caninum isolates (Nc-1, Nc-Liverpool, Nc-SweB1 and the Spanish isolates: Nc-Spain 3H, Nc-Spain 4H, Nc-Spain 6, Nc-Spain 7 and Nc-Spain 9) was studied in an in vitro model based on a placental trophoblast-derived BeWo cell line. Here, we describe that infection of dendritic cells (DC) by N. caninum tachyzoites potentiated translocation of parasites across polarized cellular monolayers. In addition, powered by the parasite's own gliding motility, extracellular N. caninum tachyzoites were able to transmigrate across cellular monolayers. Altogether, the presented data provides evidence of two putative complementary pathways utilized by N. caninum, in an isolate-specific fashion, for passage of restrictive cellular barriers. Interestingly, adoptive transfer of tachyzoite-infected DC in mice resulted in increased parasitic loads in various organs, e.g. the central nervous system, compared to infections with free parasites. Inoculation of pregnant mice with infected DC resulted in an accentuated vertical transmission to the offspring with increased parasitic loads and neonatal mortality. These findings reveal that N. caninum exploits the natural cell trafficking pathways in the host to cross cellular barriers and disseminate to deep tissues. The findings are indicative of conserved dissemination strategies among coccidian apicomplexan parasites.